Finite element analysis of an offshore jacket structure - Wong, Kin Hua. (2010)
This paper investigates the finite element study of static structural loading of forces acting on a single leg of an offshore jacket structure. ANSYS suite version 12.0 is used to create the finite element modeling and analysis of the jack up leg. The jack up leg model is subjected to environmental forces in the transverse direction at the top location and stress loading due to the weight of the hull acting in the vertical direction; suitable boundary conditions are set in place to simulate a jack up leg which is fully fixed at the bottom of the sea bed. The jack up leg is meshed with pipe16 elements and finer regions of mesh are established nearer to the bottom of the jack up leg where it is attached to the spud can.